2014
DOI: 10.1177/0954408914539940
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational analysis of the feed accelerator for a decanter centrifuge

Abstract: Industrial decanter centrifuges are used in a wide range of industries to separate mixtures of solids and liquids. One of the main elements of these devices is the feed accelerator, which accelerates the incoming mixture to the high rotational speed required for separation. A well-designed feed accelerator can increase product throughput, solids recovery, and liquid clarity, while a poorly designed accelerator can increase wear and reduce the overall efficiency of the machine. This article presents experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this regard, Tan 17 conducted numerical simulations to optimize the design of the accelerating disc in a bipolar piston pusher and designed an accelerating disc to enhance the instantaneous velocity of particles by changing the disc structure and the blade geometry. G. Bell 18 conducted experimental and computational assessments of six feed accelerator designs utilized in decanter centrifuges. Additionally, a parametric study of drum and disc accelerators was carried out using computational models.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Tan 17 conducted numerical simulations to optimize the design of the accelerating disc in a bipolar piston pusher and designed an accelerating disc to enhance the instantaneous velocity of particles by changing the disc structure and the blade geometry. G. Bell 18 conducted experimental and computational assessments of six feed accelerator designs utilized in decanter centrifuges. Additionally, a parametric study of drum and disc accelerators was carried out using computational models.…”
Section: Introductionmentioning
confidence: 99%
“…Wang 10 studied the slow diffusion of drilling fluid feed and tangential velocity lag phenomenon and optimized the decanter centrifuge structure to improve the settling velocity, separation performance, and throughput of the decanter centrifuge. Bell 11 presents experimental and computational quantification of the performance of six feed accelerator designs that are currently used in decanter centrifuges and found that increasing the surface area of the port faces of the drum accelerator and increasing the discharge angle and discharge radius for the disk accelerator improved the performance of the accelerators. Demoz 12 found that feeding preflocculated material obviates the flocculation step inside the decanter centrifuge resulting in improved process efficiency by reducing the power consumption and increasing the throughput capacity of each decanter centrifuge.…”
Section: Introductionmentioning
confidence: 99%